The Relationship Between Knowledge and Social Support With Disaster Preparedness Behaviors in Surabaya - Dewi, Yulis Setiya; Wahyuni, Erna Dwi; Alfaruq, Muhammad Fikri; Lutfiyah, Kharisma Nuur (Universitas Airlangga, 2024)
Introduction: Active faults in Surabaya move at 0.05 millimeters per year, causing earthquakes. Disaster preparedness is crucial for safety, reducing risks, enhance capabilities, and mitigate the impact of disasters. This study analyzes the relationship between knowledge, social support, and earthquake preparedness in Surabaya using the Precede-Proceed model. Methods: The method used in this study was correlational design with a cross-sectional approach. The total population of the study was 11,062 Ngagel residents, and a sample of 386 respondents from the Ngagel district was selected through purposive sampling. The independent variables in this study were knowledge and social support, while the dependent variable was the disaster preparedness behaviors of the local residents in facing earthquakes. The data were collected through a questionnaire and analyzed with logistic regression tests with a significance level of pâ‰¤0.05. Results: The analysis results showed that there was a significant relationship between knowledge (p=0.000) and social support (p=0.000) with disaster preparedness behaviors. Conclusion: Knowledge and social support have a positive relationship with disaster preparedness behavior, indicating a direct correlation. It is hoped that future researchers can conduct research with a wider range and add other factors that can initiate maladaptive responses.